The effect of consumption values on customer satisfaction of living room furniture in Saudi Arabia - AbdulRahman Makkawi, Fattwo; Hashim, Ahmad Hariza; Leby Lau, Jasmine (Thammasat University, 2022)
The living room in Saudi Arabia context is the centre of the house and makes up the main space, and is the most used room by Saudi women. Hence, satisfaction with furniture is crucial for working women as they carry on doing activities as they return from work. This paper investigates the factors that affect a working woman when purchasing furniture for the living room in Jeddah, Saudi Arabia. Multistage sampling was employed, in which 350 women working in three government sectors in Jeddah: schools, universities, and health sectors were selected for this study. The respondents received the questionnaire through emails, and reliability and normality tests were applied. The multiple regression test examined the consumption values predictors on furniture satisfaction. The results revealed that conditional, functional, and emotional values significantly correlated with the satisfaction of working women with the furniture in the living room. Conversely, epistemic and social values had an insignificant relationship. This paper provides a clearer insight into the prominent consumption values variables that significantly affect the furniture satisfaction of working women in their living rooms. Therefore, this study can exhibit and enhance the lifestyle of more working women and help them achieve work-life balance using living room furniture by acquiring better knowledge and understanding of consumption values.